Ecological factors affecting brine shrimps availability in the salt pans of north coastal districts of Maharashtra - Meenatchi S; Abuthagir I. S; Manjusha L; Jerusha S; Jaiswar A.K; Nayak. B. B (Journal of Indian Fisheries Association, 2022)
Salt pans are a unique ecological habitat for numerous macroscopic and microscopic organisms. Mysids, copepods, ciliates, brine shrimp, and phytoplankton are essential organisms in India’s salt pan ecosystems. Most of these organisms are identified as potential live feeds for other larger aquatic organisms due their natural preference. Brine shrimps are one group of organisms that are present in most of the saltpans. Following the increase in shrimp aquaculture the imported brine shrimps have entered the coastal waters. To examine local waterbodies of saltpans for their presence this study was undertaken between January to June 2022, and the sampling area included saltpans of Bhayandar, Morva, Saphale, Bhandup, Thane, Wadala, Raigaon, Naigaon and Mulund from north coastal districts of Maharashtra. Samples were collected using a circular hand net with a length of 0.5 m, a mouth area of 0.04 m2, and a mesh size of 40 microns. The filtered samples were examined under a light microscope to identify the different zooplankton. Urbanization causes the reduction of salt pans in major cities and brings considerable changes in the saltpans. This study reports the absence of artemia, after exhaustive sampling though earlier studies in the same study area have reported the presence of artemia in the places of Bhayandar, Bhandup, Thane and Morva during January to June 2022. We tried to find the reason behind the absence of Artemia from the sampling sites.